Adverse Drug Reaction (ADR) of Hydroxychloroquine(HCQ) in the -Preexposure Prophylaxis (PrEP) of COVID-19 in Health Care Professionals in a Tertiary Care Teaching Hospital - Pranav S Jadhav; Saleem B Tamboli; Rahul B Parsode (Journal of Pharmaceutical Research)
In December 2019 an outbreak of emerging COVID-19 due to the SARS CoV-2 infection started in Wuhan, China and rapidly spread throughout the world. WHO declared COVID-19 as PANDEMIC on 12th March 2020. Various drugs were introduced to treat and prevent this pandemic. Hydroxychloroquine gained widespread attention due to its antiviral action and inhibitory effect. HCQ was preferred which has antiviral effect similar to that of Chloroquine. ICMR and FDA has advocated their use in severe COVID-19 disease. There are uncertain and limited data to support the beneficial effect of this drug. Our study was aimed to investigate the adverse drug reaction of HCQ given prophylactically for COVID-19 to the health care professional. After taking ethical committee approval, a study was conducted among the health care professional from 1st April 2020 to 31st May 2020. The participants were given an online pretested, validated questionnaire to ascertain the adverse effects while taking HCQ. Due to the nature of COVID-19 and restrictions on personal interview and examination, only online symptom questionnaire for adverse effects was given. 183 participants were involved in the study who were working as a health care professional in COVID-19. Out of these 9 participants were excluded based on the exclusion criteria. 73 adverse drug reaction were found in 56 participants. Most common and frequent side effects were headache, nausea, loose stools and dizziness. Almost 22 participants required some painkillers to treat the adverse effects. Data was entered in MS Excel and presented in the form of frequencies and percentages. Almost 32.18% reported adverse effects. So utmost care should be taken before using HCQ prophylactically in health care professionals working in COVID-19. Keywords Adverse Drug Reaction, Preexposure Prophylaxis, COVID 19, Hydroxychloroquine, Health Care Professionals